Predictive Analysis of Mutual Fund Investment Using Sustainability Index Evidence from Indian Stock Market - et. al., Heera S Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is an attempt to predict the price movement between S & P BSE GREENEX and selected open ended equity mutual fund categories traded at stock exchanges in India. Daily data over the last 5 years were taken and the sample period is from January 1, 2016 to January 1, 2021. The authors use a set of econometric models such as dynamic lag vector auto regression stochastic process model, Cointegration, Granger causality test and Variance Decomposition to substantiate the existence of long run and short run association between the dependent and independent variables selected. The study shows clear evidences of cointegration between S & P BSE GREENEX and selected mutual fund categories, which is an indication of the existence of long run equilibrium relationship between the variables. The empirical investigation also proved the traces of bi-directional and uni-directional Granger- casual effect between the variables. The findings of the study show that S & P BSE GREENEX and large cap mutual fund categories have strong price movement relationship compared to mid-cap funds, which shows a marginal relationship and relatively very weak relationship with small cap funds.